Diagnostic accuracy of computer morphometry for steatosis and fibrosis assessment in patients with chronic liver disease of various etiologies - Yu.M. Stepanov; V.I. Didenko; Yu.A. Gaydar; N.Yu. Zavhorodnia; O.P. Petishko (Gastroenterologìa, 2023)
Background. Accurate assessment of the fibrosis stage is crucial for effective treatment. Histological examination, the primary method used for assessing liver fibrosis, has certain limitations due to variation within each stage. Computer morphometry offers an objective and quantitative approach to complement histological analysis, providing additional diagnostic information. The purpose of this study was to analyze the computer morphometry data in patients with chronic liver diseases (CLD) of different etiologies and determine their diagnostic accuracy for liver fibrosis diagnosis. Materials and methods. Seventy-five patients with CLD, namely 24 with non-alcoholic fatty liver disease (NAFLD), 8 with alcoholic liver disease (ALD), 1 with toxic hepatitis, and 42 with chronic hepatitis C (CHC), were included in the study. Percutaneous liver biopsy was performed under ultrasound guidance using a semi-automatic needle Colt Shot 16 G. The severity of fibrosis was assessed using the Metavir scale. For computer morphometry, biopsies were photographed and evaluated using the ImageJ 1.45S program (National Institutes of Health, USA). The computerized fibrosis index (CFI), steatosis index, and the number of apoptotic cells in 5 consecutive high-power fields were calculated. Receiver operating characteristic analysis was performed for CFI diagnostic accuracy assessment. Results. Advanced liver fibrosis (F3-F4) was diagnosed in 62.5 % of ALD cases and 31.0 % of CHC. The highest CFI was found in ALD, it exceeded the level of NAFLD and CHC patients by 3.3 (p < 0.01) and 2 times (p < 0.05), respectively. At the same time, people with NAFLD had the highest steatosis index (0.36 ± 0.11), which was 1.7 times higher (p < 0.05) than in ALD and CHC. Moreover, CFI correlated with the fibrosis stage (r = 0.71, p < 0.05). Stage I of liver fibrosis according to the Metavir scale is characterized by CFI up to 0.040, stage II — 0.041–0.130, stage III — 0.131–0.219, and stage IV — more than 0.220. CFI cut-off value was 0.017, which confirms the presence of liver fibrosis in patients with chronic liver diseases regardless of the etiology (sensitivity — 85.2 %, specificity — 100.0 %). Conclusions. Computer morphometry significantly improves the accuracy and reliability of histological examination, and allows to objectify morphological assessment of liver steatosis and fibrosis and to ensure long-term storage of the results.